On the role of seasonal intercepts in seasonal cointegration - Philip Hans Franses; Robert M. Kunst (Institute for Advanced Studies (IHS), 1995)
In the paper we consider the role of seasonal intercepts in seasonal cointegration analysis. For the nonseasonal unit root, such intercepts can generate a stochastic trend with a drift common to all observations. For the seasonal unit roots, however, we show that unrestricted seasonal intercepts generate trends that are different across the seasons. Since such seasonal trends may not appear in economic data, we propose a modified empirical method to test for seasonal cointegration. This method is illustrated on German consumption and income data. – – Im Papier erwägen wir die Rolle saisonaler Regressionskonstanten in der Analyse saisonaler Kointegration. Für die nichtsaisonale Einheitswurzel können solche Konstanten stochastische Trends mit gemeinsamer Drift generieren. Für saisonale Einheitswurzeln zeigen wir jedoch, dass unrestringierte Saisonkonstanten Trends erzeugen, die über die Jahreszeiten unterschiedlich sind. Da solche wohl in ökonomische Daten nicht auftreten, schlagen wir eine veränderte empirische Methode vor, um auf saisonale Kointegration zu testen. Diese Methode wird anhand deutscher Konsum- und Investitionsdaten dargebracht.
Keywords: C32; 330; deterministic and stochastic seasonality; seasonal cointegration; cointegration; Zeitreihenanalyse; Theorie; Saisonschwankung